PERAN HIKAYAT ACEH SEBAGAI MEDIA DALAM PELESTARIAN DAN PEMAJUAN BUDAYA LOKAL - Hasbi; Saiful Bahgia (JURNAL KREASI RAKYAT, 2024)
This study aims to analyze the role of Hikayat Aceh as a medium for preserving and advancing local Acehnese culture. Hikayat Aceh is a classic literary work that contains historical, religious, social, and customary values ​​of the Acehnese people during the heyday of the Aceh Sultanate. Through a qualitative approach with literature study and content analysis methods, this study found that Hikayat Aceh plays an important role in documenting the cultural identity of the Acehnese people, including language, value systems, leadership, and local traditions. In addition, this saga also has great potential in character education, especially in instilling religious values, leadership, patriotism, and social ethics in the younger generation. However, the preservation of this saga faces various challenges such as low interest in reading classical literature, lack of integration in the education curriculum, and minimal digitization of manuscripts. Therefore, collaborative efforts are needed between the government, academics, and the community to revive the role of Hikayat Aceh as a source of living culture that is able to answer the challenges of the times while strengthening local cultural identity.